Cu-NiZnFeO catalyst, preparation method thereof and application of Cu-NiZnFeO catalyst in preparation of methanol through CO2 hydrogenation

By using Cu-NiZnFeO catalyst, the molar ratio and content of Cu, Ni, Zn and Fe elements were prepared and optimized by the double drop method, and the problems of low CO2 conversion and methanol selectivity of the existing CO2 hydrogenation catalyst were solved. It has achieved efficient CO2 conversion and methanol selectivity, and has good industrial application value.

CN119406414APending Publication Date: 2025-02-11CIMC ENRIC ENGINEERING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411504033.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing CO2 conversion rate and methanol selectivity of the hydrogenation catalyst for CO2 are low, and the high reaction temperature will accelerate the RWGS reaction and lead to an increase in H2 consumption.

Method used

Cu-NiZnFeO catalyst is used, which is prepared by a double drop method, and reacts with a mixed metal salt solution of Cu2+, Zn2+, Ni2+ and Fe3+ with a mixed alkali solution of CO32- and OH- to obtain the active component after calcination and in-situ reduction. Cu+, Cu0 and Ni0, cocatalyst ZnO and support Fe2O3, optimize the molar ratio and content of Cu, Ni, Zn and Fe elements.

Benefits of technology

The CO2 conversion rate and methanol selectivity are significantly improved. The CO2 conversion rate reaches at least 15.5%, the methanol selectivity reaches at least 89.5%, and the maximum can reach 98.2%. The catalyst preparation process is simple, green and environmentally friendly, low-cost, and has Good industrial application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119406414A_ABST
    Figure CN119406414A_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-NiZnFeO catalyst, which is prepared by the following steps: by taking a mixed metal salt solution of Cu < 2 + >, Zn < 2 + >, Ni < 2 + > and Fe < 3 + > and a mixed alkali solution of CO3 < 2-> and OH <-> as raw materials, preparing quaternary hydrotalcite CuNiZnFe-LDH by adopting a double-dropping method, calcining the CuNiZnFe-LDH to obtain a catalyst precursor CuNiZnFe-LDO, and performing in-situ reduction on the catalyst precursor CuNiZnFe-LDO to obtain the Cu-NiZnFeO catalyst. In the preparation process of the Cu-NiZnFeO catalyst, atoms of hydrotalcite are arranged on fixed crystal lattices, electrostatic attraction between reduced Cu can be effectively prevented, agglomeration of active components on the surface of the catalyst due to electrostatic attraction is avoided, and the content of the effective active components of the catalyst is increased. The invention also discloses an application of the Cu-NiZnFeO catalyst in preparation of methanol through CO2 hydrogenation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic hydrogenation, and relates to a quaternary metal oxide and a preparation method thereof and a method for preparing methanol by hydrogenating CO2, and specifically relates to a Cu-NiZnFeO catalyst and a preparation method thereof and application in preparing methanol by hydrogenating CO2. Background Art

[0002] To achieve the recycling of carbon resources, turning green, abundant and renewable CO2 into treasure and converting it into high-value utilization of methanol has a broad application market. The development and utilization of green energy has become an important issue in today's society, and the emergence of CO2 to green methanol technology provides us with a sustainable development solution. According to the Le-Chatelier principle, high temperature and low pressure operating conditions are conducive to the production of methanol. However, high reaction temperature will accelerate the RWGS reaction (CO2+H2→CO+H2O), resulting in H2 consumption and reduced methanol yield. The thermodynamic properties of the CO2 hydrogenation to methanol reaction determine that its equilibrium methanol yield is low. Therefore, it is of great significance to develop an efficient CO2 hydrogenation to methanol catalyst.

[0003] However, CO2 is in the highest oxidation state. Considering the chemical inertness and reaction rate of CO2, a reaction temperature above 240°C is generally used to activate CO2 and generate methanol. At present, the catalysts for CO2 hydrogenation to methanol are mainly Cu / Zn / Al2O3 ternary catalysts, copper-based multi-catalysts, palladium-based catalysts, and low-temperature-gas-liquid phase catalysts copper-based catalysts. Cu / Zn / Al2O3 ternary catalysts have high selectivity for methanol. Among them, Cu / Zn as the active site of the methanol catalyst plays a key role in the generation of methanol, but the CO2 conversion rate and methanol selectivity are not high. Since Cu / Zn-based catalysts have certain activity and stability, and are cheap, they are still widely used in industry. Therefore, in order to increase the CO2 conversion rate, it is necessary to optimize the design of Cu / Zn-based methanolization catalysts to maximize the methanol yield. Summary of the invention

[0004] In view of the above-mentioned problems in the prior art, the present invention provides a Cu-NiZnFeO catalyst and its application in CO2 hydrogenation to methanol.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A Cu-NiZnFeO catalyst, which is based on Cu 2+ 、Zn 2+ 、Ni 2+ and Fe 3+ Mixed metal salt solution and CO3 2- and OH -The mixed alkaline solution of is used as a raw material, and a quaternary hydrotalcite CuNiZnFe-LDH is prepared by a double drop method. The CuNiZnFe-LDH is calcined to obtain a catalyst precursor CuNiZnFe-LDO, and the catalyst precursor CuNiZnFe-LDO is then reduced in situ to obtain CuO in the CuNiZnFe-LDO, and NiO is reduced to Ni. The raw materials are weighed according to the following dosage relationship: the molar ratio of the total amount of Cu, Ni and Zn elements to the Fe element is 3:1, the molar percentage of the Cu element in the total amount of the four elements of Cu, Ni, Zn and Fe is 25-65%, and the molar percentage of the Ni element in the total amount of the four elements of Cu, Ni, Zn and Fe is 2-6%.

[0007] In the Cu-NiZnFeO catalyst, the active component is Cu + , Cu 0 And Ni 0 The catalytic active component is ZnO. Fe2O3 as a carrier not only provides support and dispersion in catalytic hydrogenation, but also promotes the electron transfer process and enhances the efficiency of the catalytic reaction, especially in the catalytic process involving redox reactions, thereby affecting the catalytic efficiency and product selectivity.

[0008] Preferably, the raw materials are weighed according to the following dosage relationship: the molar ratio of the total amount of Cu, Ni and Zn elements to the Fe element is 3:1, the molar percentage of Cu element in the total amount of Cu, Ni, Zn and Fe is 25-45%; the molar percentage of Ni element in the total amount of Cu, Ni, Zn and Fe is 5%.

[0009] More preferably, the raw materials are weighed according to the following dosage relationship: the molar ratio of the total amount of Cu, Ni and Zn elements to the Fe element is 3:1, the molar percentage of Cu element in the total amount of Cu, Ni, Zn and Fe is 35-45%; the molar percentage of Ni element in the total amount of Cu, Ni, Zn and Fe is 5%.

[0010] Most preferably, the raw materials are weighed according to the following dosage relationship: the molar ratio of the total amount of Cu, Ni and Zn elements to the Fe element is 3:1, the molar percentage of Cu element in the total amount of Cu, Ni, Zn and Fe is 45%; the molar percentage of Ni element in the total amount of Cu, Ni, Zn and Fe is 5%.

[0011] Preferably, the metal mixed salt solution is selected from Cu 2+ One of nitrates, chlorides or sulfates selected from Zn 2+ One of nitrates, chlorides or sulfates, selected from Ni 2+One of nitrates, chlorides or sulfates selected from Fe 3+ A mixed aqueous solution of one of the nitrates, chlorides or sulfates of

[0012] Preferably, the mixed alkaline solution is a mixed aqueous solution of Na2CO3 and NaOH.

[0013] Preferably, CO3 2- The amount of substance satisfy: The OH - The amount of substance satisfy: in, Cu 2+ 、Ni 2+ 、Zn 2+ The total amount of substance; Fe 3+ The amount of substance.

[0014] Specifically, in the mixed metal salt solution, Cu 2+ 、Zn 2+ 、Ni 2+ and Fe 3+ The total molar concentration of the substance is 1 mol / L; in the mixed alkali solution, CO3 2- The molar concentration of OH is 2.65~2.68mol / L. - The molar concentration is 0.8~0.85mol / L.

[0015] Another object of the present invention is to provide a method for preparing the Cu-NiZnFeO catalyst, comprising: using a double drop method to mix a mixed metal salt solution and a mixed alkali solution for reaction, followed by aging, to obtain a precipitate of CuNiZnFe-LDH; calcining the CuNiZnFe-LDH to obtain a catalyst precursor CuNiZnFe-LDO, and then reducing the solution in situ to obtain a Cu-NiZnFeO catalyst; wherein the solution A is Cu 2+ 、Zn 2+ 、Ni 2+ and Fe 3+ A mixed aqueous solution; the solution B is CO3 2- and OH - of a mixed aqueous solution.

[0016] Preferably, the temperature of the mixed reaction is 55-65° C., the mixed reaction time is 1 hour, and the pH of the mixed reaction is 9-10.

[0017] Preferably, the aging temperature is 55-65° C., and the aging time is 6-10 hours.

[0018] Preferably, the calcination temperature is 200-400° C., the calcination time is 1-5 hours, and the calcination is carried out in a muffle furnace.

[0019] More preferably, the calcination is: heating from room temperature to 200-400° C. at a heating rate of 5° C. / min, and calcining at a temperature of 200-400° C. for 1-5 hours.

[0020] Preferably, the environment of the in-situ reduction is: the reducing gas is a 50% H2 / N2 mixed gas, the reducing temperature is 200-300°C, preferably 260-280°C, and the reducing time is 2-8h, preferably 4h.

[0021] More preferably, the catalyst precursor CuNiZnFe-LDO is pressed into tablets and then subjected to in-situ reduction.

[0022] The in-situ reduction is carried out in a fixed bed, and specifically a three-stage temperature-controlled fixed bed can be selected.

[0023] As a preferred technical solution of the preparation method of the Cu-NiZnFeO catalyst, it also includes: after aging, filtering or centrifuging to separate the precipitate, washing the precipitate with water until the pH value of the filtrate is 7, and then drying and grinding in sequence to obtain CuNiZnFe-LDH.

[0024] Preferably, the drying method is drying or freeze drying. The drying temperature is 80-110° C. and the drying time is 12-24 hours.

[0025] Specifically, a method for preparing the Cu-NiZnFeO catalyst comprises the following steps:

[0026] Step (1), using a double drop method to simultaneously titrate a mixed metal salt solution and a mixed alkali solution into a reaction device, maintaining the pH at 9-10 during the titration process; filtering or centrifuging to separate a precipitate, washing the precipitate with water until the pH of the filtrate is 7, and then drying and grinding in sequence to obtain CuNiZnFe-LDH;

[0027] Step (2), placing CuNiZnFe-LDH in a muffle furnace, heating the temperature from room temperature to 200-400°C at a heating rate of 5°C / min, and calcining at a temperature of 200-400°C to obtain a catalyst precursor CuNiZnFe-LDO;

[0028] Step (3), placing the catalyst precursor CuNiZnFe-LDO in a fixed bed for in-situ reduction to obtain a Cu-NiZnFeO catalyst.

[0029] Another object of the present invention is to provide the use of the Cu-NiZnFeO catalyst in the preparation of methanol by CO2 hydrogenation.

[0030] A method for preparing methanol by hydrogenation of CO2, comprising: using the Cu-NiZnFeO catalyst to catalyze the hydrogenation reaction of CO2 and hydrogen to obtain methanol; wherein the reaction gas is a mixed gas with a volume ratio of H2 to CO2 of 3:1 to 8:1, the reaction temperature is 200 to 300°C, the reaction pressure is 2 to 5 MPa, and the reaction space velocity is 500 to 20000 h -1 .

[0031] Preferably, the reaction gas is a mixture of H2 and CO2 in a volume ratio of 3:1 to 3.5:1.

[0032] Preferably, the reaction temperature is 240-250°C, the reaction pressure is 3-3.2 MPa, and the reaction space velocity is 6500-7600 h -1 .

[0033] The beneficial effects of the present invention are:

[0034] (1) The Cu-NiZnFeO catalyst of the present invention is a bimetallic catalyst, and the active component is Cu + and Cu 0 and Ni 0 , ZnO is the co-catalyst component, and Fe2O3 is used as a carrier. In the preparation process of Cu-NiZnFeO catalyst, the atoms of hydrotalcite are arranged on a fixed lattice, which can effectively prevent the electrostatic attraction between Cu after reduction, avoid the agglomeration of Cu-Ni dual active components on the catalyst surface due to electrostatic attraction, and the active components have good dispersion, which increases the effective active component content of the catalyst and greatly saves the cost of raw materials.

[0035] (2) There is a strong chemical interaction between the components in the Cu-NiZnFeO catalyst of the present invention, which enhances the interaction between the metal and the oxide, making the active center difficult to fall off and lose.

[0036] (3) The preparation process of the catalyst of the present invention is simple, green and environmentally friendly, and has low cost and high atom economic benefits.

[0037] (4) The catalyst of the present invention has good temperature resistance, is not easy to coke, can be recycled many times, and has good industrial application value.

[0038] (5) The Cu-NiZnFeO catalyst of the present invention is used to catalyze the hydrogenation of CO2 to produce methanol. The catalyst has high catalytic activity and significantly improves the conversion rate of CO2 and the selectivity of the product methanol. Under the action of the Cu-NiZnFeO catalyst, the conversion rate of CO2 reaches at least about 15.5% after 120 hours of steady state, and the selectivity of methanol reaches at least about 89.5%, and can reach a maximum of about 98.2%; and the process is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 (a) and (b) the XRD pattern of CuNiZnFe-LDH and CuNiZnFe-LDO prepared in Example 1.

[0040] Figure 2 These are SEM images and TEM images of CuNiZnFe-LDH and CuNiZnFe-LDO prepared in Example 1; wherein a is the SEM image of CuNiZnFe-LDH, b is the SEM image of CuNiZnFe-LDO, c is the TEM image of CuNiZnFe-LDH, and d is the TEM image of CuNiZnFe-LDO.

[0041] Figure 3 (a) and (b) the adsorption-desorption curves of CuNiZnFe-LDH and CuNiZnFe-LDO prepared in Example 1.

[0042] Figure 4 : This is the XPS spectrum of each element in the CuNiZnFe-LDO prepared in Example 1; wherein a is the XPS spectrum of the Cu 2p orbital, b is the XPS spectrum of the O1s orbital, c is the XPS spectrum of the Fe 2p orbital, d is the XPS spectrum of the Ni 2p orbital, and e is the XPS spectrum of the Zn2p orbital. DETAILED DESCRIPTION

[0043] The technical scheme of the present invention will be described in more detail below through examples, but these examples do not limit the protection scope of the present invention.

[0044] The molar content of copper is the molar percentage of the Cu element in the metal salt raw material to the total amount of Cu, Ni, Zn, and Fe; the molar content of nickel is the molar percentage of the Ni element in the metal salt raw material to the total amount of Cu, Ni, Zn, and Fe.

[0045] Example 1

[0046] According to the molar ratio of metal elements copper, nickel, zinc and iron of 1.8:0.2:1:1, 10.872g Cu(NO3)2·3H2O, 1.454g Ni(NO3)2·6H2O, 7.44g Zn(NO3)2·6H2O and 10.1g Fe(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare mixed salt solution A.

[0047] According to the formula Calculate the amount of NaOH according to the formula Calculate the amount of Na2CO3, dissolve 6.4g NaOH and 5.3g Na2CO3 in 60mL deionized water to prepare mixed alkaline solution B.

[0048] About 10 mL of deionized water was added to a four-necked flask in advance, and the mixture was heated to 60°C. The mixed salt solution A and the mixed alkali solution B were added to the flask at the same time under stirring conditions, and the addition was completed within 1 hour. The pH of the mixed solution was always kept at 9-10 during the addition process. After the addition was completed, the mixture was aged at 60°C and stirred for 6 hours, filtered, and the filter cake was washed with deionized water until the pH of the filtrate was 7. The filter cake was dried in an oven at 105°C for 24 hours to obtain CuNiZnFe-LDH. The CuNiZnFe-LDH was ground into powder, and the powder was placed in a muffle furnace, and the temperature was increased from room temperature to 350°C at a heating rate of 5°C / min, and calcined at 350°C for 4 hours to obtain a catalyst precursor CuNiZnFe-LDO; the catalyst precursor CuNiZnFe-LDO was reduced in situ to obtain a reduced Cu-NiZnFeO catalyst. The molar content of copper in the Cu-NiZnFeO catalyst is 45%, and the molar content of nickel is 5%.

[0049] The in-situ reduction method is as follows: 4 g of quartz sand with a mesh size of 40 to 60 is weighed and filled into the packing layer of a stainless steel reaction tube with an inner diameter of 1 cm, then 1 g of Cu-NiZnFeO catalyst precursor is weighed and pressed into a tablet and placed on the quartz sand, and finally 4 g of quartz sand with a mesh size of 40 to 60 is filled into the packing layer of the reaction tube; a 50% H2 / N2 mixed gas is introduced at an air velocity of about 4000 h -1 The reduction temperature is about 280℃ and maintained for 4h.

[0050] The XRD patterns of the prepared CuNiZnFe-LDH and Cu-NiZnFeO are shown in Figure 1As shown in a, three characteristic peaks appear at 28.6°, 36.2° and 47.8°, which are characteristic peaks of CuNiZnFe-LDH hydrotalcite. These three peaks represent the characteristic diffraction peaks of the hydrotalcite crystal surface, indicating that CuNiZnFe-LDH has been successfully synthesized and a complete layered structure belonging to hydrotalcite has been formed. From the figure, it can be seen that these 28.6° diffraction peaks are relatively sharp, indicating that the synthesized CuNiZnFe-LDH has high purity and good crystallinity; after high-temperature calcination, the original structure of CuNiZnFe is destroyed and converted into an amorphous structure, the layered structure is destroyed, and the characteristic peaks disappear.

[0051] The FT-IR images of the prepared CuNiZnFe-LDH and CuNiZnFe-LDO are shown in Figure 1 As shown in b, it can be seen that 3460cm -1 A broadband absorption band appeared, indicating that the interlayer OH - Existence, 1634cm -1 The peak at 1377 cm -1 The nearby vibration peaks are due to the asymmetric stretching vibrations of carbonates.

[0052] The SEM images of the prepared CuNiZnFe-LDH and CuNiZnFe-LDO are shown in Figure 2 a. Figure 2 As shown in b, the TEM images are Figure 2 c. Figure 2 As shown in d, the morphology of the samples before and after calcination can be observed by SEM and TEM. Figure 2 a. Figure 2 c It can be seen that CuNiZnFe-LDH presents a typical layered structure (petal-shaped layered structure), while the layered crystal structure of CuNiZnFe-LDO obtained after calcination is somewhat collapsed ( Figure 2 b), forming scattered clumps, but the basic layered structure still exists ( Figure 2 d).

[0053] The N2 adsorption-desorption curves of the prepared CuNiZnFe-LDH and CuNiZnFe-LDO are shown in Figure 3 a, are typical type IV isotherms, and there is an H3 type hysteresis loop, indicating that the mesoporous pores are maintained after heat treatment. The pore size distribution diagram of CuNiZnFe-LDH and CuNiZnFe-LDO is shown in Figure 3 b, it can be seen that the pore sizes of CuNiZnFe-LDH and CuNiZnFe-LDO are both between 0 and 5 nm, which is consistent with the analysis of the N2 adsorption-desorption isotherms.

[0054] The XPS patterns of Cu 2p, O 1s, Fe 2p, Ni 2p and Zn 2p of the prepared Cu-NiZnFeO are shown in Figure 4 a. Figure 4 b. Figure 4 c. Figure 4 d. Figure 4 As shown in e. Figure 4 a It can be seen that the Cu 2p orbital is observed near 934.8 eV. 2+ 2p 3 / 2 The characteristic peak of Cu ions was observed around 933.1 eV. + / Cu 0 The peak of O 1s orbit is observed at 941~944eV. Figure 4 b, Oxygen species were observed on the catalyst surface at three positions with binding energies of 532.6eV, 531.2eV and 530.1eV, 532.6eV corresponds to oxygen adsorbed by surface water or carbonate, 531.2eV corresponds to oxygen chemically adsorbed on the surface, and 531.8eV corresponds to lattice oxygen in the catalyst. Figure 4 c, Two main peaks and one energy peak were observed in the range of 710-730 eV. The peak observed at 710.7 eV corresponds to Fe 2p 3 / 2 , while the peak observed at 723.8 eV corresponds to Fe 2p 3 / 1 , the energy peak observed at 718.8 eV corresponds to Fe 3+ . Ni 2p orbitals see Figure 4 d, 855.3eV and 861eV correspond to Ni 2+ ; Two peaks observed from Zn2p orbital ( Figure 4 e), 1021.7eV and 1044.8eV are attributed to Zn 2p 3 / 2 and Zn 2p 1 / 2 .

[0055] Catalyst performance evaluation: 4 g of quartz sand with a mesh size of 40-60 was weighed and filled into the packing layer of a stainless steel reaction tube with an inner diameter of 1 cm. Then 1 g of the catalyst precursor CuNiZnFe-LDO was weighed and pressed into a tablet and placed on the quartz sand. Finally, 4 g of quartz sand with a mesh size of 40-60 was filled into the packing layer of the reaction tube. A 50% H2 / N2 mixed gas was introduced at an air velocity of about 4000 h -1 The reduction temperature is about 280°C, maintained for 4 hours, and the reduced Cu-NiZnFeO catalyst is obtained; the temperature is raised to 240°C, and hydrogen and carbon dioxide are introduced as reaction gases in a volume ratio of 3.5:1. The pressure is 3 MPa and the reaction space velocity is 7600 h -1The catalytic carbon dioxide hydrogenation experiment was carried out under the conditions of ; after 120h steady state, the CO2 conversion rate was 18.6% and the methanol selectivity was 98.2%.

[0056] Example 2

[0057] According to the molar ratio of metal elements copper, nickel, zinc and iron of 1.0:0.2:1.8:1, 6.04g Cu(NO3)2·3H2O, 1.45g Ni(NO3)2·6H2O, 13.086g Zn(NO3)2·6H2O and 10.1g Fe(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare mixed salt solution A.

[0058] According to the formula Calculate the amount of NaOH according to the formula Calculate the amount of Na2CO3, dissolve 6.4g NaOH and 5.3g Na2CO3 in 60mL deionized water to prepare mixed alkaline solution B.

[0059] About 10 mL of deionized water was added to a four-necked flask in advance, and the mixture was heated to 60°C. Solution A and solution B were added to the flask at the same time under stirring conditions, and the addition was completed within 1 hour. The pH of the mixed solution was always kept at 9-10 during the addition process. After the addition was completed, the mixture was stirred continuously and aged at 60°C for 6 hours. After the aging was completed, the mixed solution was filtered, and the filter cake was washed with deionized water until the pH of the filtrate was 7, and then dried in an oven at 105°C for 24 hours to obtain CuNiZnFe-LDH, which was ground into powder, placed in a muffle furnace, heated from room temperature to 300°C at a heating rate of 5°C / min, and calcined at 300°C for 4 hours to obtain a catalyst precursor CuNiZnFe-LDO; the catalyst precursor CuNiZnFe-LDO was reduced in situ to obtain a reduced Cu-NiZnFeO catalyst. The molar content of copper in the Cu-NiZnFeO catalyst was 25%, and the molar content of nickel was 5%.

[0060] Catalyst performance evaluation: 4 g of quartz sand with a mesh size of 40-60 was weighed and filled into the packing layer of a stainless steel reaction tube with an inner diameter of 1 cm. Then 1 g of the catalyst precursor CuNiZnFe-LDO was weighed and pressed into a tablet and placed on the quartz sand. Finally, 4 g of quartz sand with a mesh size of 40-60 was filled into the packing layer of the reaction tube. A 50% H2 / N2 mixed gas was introduced at an air velocity of about 4000 h -1 The reduction temperature is about 260°C, maintained for 4 hours, and the reduced Cu-NiZnFeO catalyst is obtained by in-situ reduction; the temperature is raised to 240°C, and hydrogen and carbon dioxide are introduced as reaction gases at a volume ratio of 3.5:1 at a pressure of 3MPa and a reaction space velocity of 6500h -1The catalytic carbon dioxide hydrogenation experiment was carried out under the conditions of ; after 120h steady state, the CO2 conversion rate was 15.7% and the methanol selectivity was 89.6%.

[0061] Example 3

[0062] According to the molar ratio of metal elements copper, nickel, zinc and iron of 1.4:0.2:1.4:1, 8.456g Cu(NO3)2·3H2O, 1.45g Ni(NO3)2·6H2O, 10.416g Zn(NO3)2·6H2O and 10.1g Fe(NO3)3·9H2O were weighed and dissolved in 100mL deionized water to prepare mixed salt solution A.

[0063] According to the formula Calculate the amount of NaOH according to the formula Calculate the amount of Na2CO3, dissolve 6.4g NaOH and 5.3g Na2CO3 in 60mL deionized water to prepare mixed alkaline solution B.

[0064] About 10 mL of deionized water was added to a four-necked flask in advance, and the mixture was heated to 60°C. Solution A and solution B were added to the flask at the same time under stirring conditions, and the addition was completed within 1 hour. The pH of the mixed solution was always kept at 9-10 during the addition process. After the addition was completed, the mixture was stirred continuously and aged at 60°C for 8 hours. After the aging was completed, the mixed solution was filtered, and the filter cake was washed with deionized water until the pH of the filtrate was 7, and then dried in an oven at 100°C for 24 hours to obtain CuNiZnFe-LDH, which was ground into powder, placed in a muffle furnace, heated from room temperature to 400°C at a heating rate of 5°C / min, and calcined at 400°C for 4 hours to obtain a catalyst precursor CuNiZnFe-LDO; the catalyst precursor CuNiZnFe-LDO was reduced in situ to obtain a reduced Cu-NiZnFeO catalyst. The molar content of copper in the Cu-NiZnFeO catalyst is 35%, and the molar content of nickel is 5%.

[0065] Catalyst performance evaluation: 4 g of quartz sand with a mesh size of 40-60 was weighed and filled into the packing layer of a stainless steel reaction tube with an inner diameter of 1 cm. Then 1 g of the catalyst precursor CuNiZnFe-LDO was weighed and pressed into a tablet and placed on the quartz sand. Finally, 4 g of quartz sand with a mesh size of 40-60 was filled into the packing layer of the reaction tube. A 50% H2 / N2 mixed gas was introduced at an air velocity of about 3500 h -1 The reduction temperature was about 270°C and maintained for 4 hours to obtain the reduced Cu-NiZnFeO catalyst by in-situ reduction. The temperature was raised to 250°C and hydrogen and carbon dioxide were introduced as reaction gases at a volume ratio of 3.0:1. The pressure was 3.2 MPa and the reaction space velocity was 7500 h -1The catalytic carbon dioxide hydrogenation experiment was carried out under the conditions of ; after 120h steady state, the CO2 conversion rate was 17.4% and the methanol selectivity was 92%.

[0066] Comparative Example 1

[0067] The preparation of Cu-NiZnO is the same as in Example 1, except that the molar ratio of the metal elements copper, nickel and zinc is 1.8:0.2:1.

[0068] The catalyst performance evaluation conditions were the same as those in Example 1. After 120 hours of steady state, the CO2 conversion rate was 13.4% and the methanol selectivity was 84%.

[0069] Comparative Example 2

[0070] The preparation of Cu-ZnO is the same as in Example 1, except that the molar ratio of the metal elements copper and zinc is 2:1.

[0071] The catalyst performance evaluation conditions were the same as those in Example 1. After 120 hours of steady state, the CO2 conversion rate was 12.2% and the methanol selectivity was 56%.

[0072] Comparative Example 3

[0073] Referring to Example 1 of patent CN111215084A, copper nitrate, zinc nitrate, aluminum nitrate, sodium carbonate and sodium hydroxide are prepared into solutions with metal ion concentration of 1 mol / L respectively by deionized water; then 100 mL of deionized water is added to the reactor as a precipitation tank, 60 mL of copper nitrate solution, 30 mL of zinc nitrate solution and 10 mL of aluminum nitrate solution are mixed, and then 210 mL of sodium hydroxide solution is mixed with the above solution, and the precipitation tank temperature is kept at 60°C and pH is 8 throughout the whole process; after precipitation is complete, stirring and aging are continued at a temperature of 60°C for 12 hours; filtering is performed to separate the obtained precipitate, and the precipitate is washed with deionized water until there is no sodium ion in the filtrate and the filtrate is neutral; at a temperature of 90°C, the washed precipitate is air-dried for 6 hours, and then roasted at a temperature of 450°C for 12 hours; finally, after grinding and tableting, a catalyst sample is obtained. The molar ratio of Cu:Zn:Al in the catalyst sample is 6:3:1, and the copper content is 60%.

[0074] The catalyst performance evaluation conditions were the same as those in Example 1. After 120 hours of steady state, the CO2 conversion rate was 16% and the methanol selectivity was 65%.

[0075] Comparative Example 4

[0076] Referring to patent CN114920623A, the preparation of Cu / ZnO / Al2O3 catalyst is as follows:

[0077] 1) Dissolve copper nitrate, zinc nitrate and aluminum nitrate in water to obtain solution 1, wherein the molar ratio of Cu:Zn:Al in solution 1 is 5:3:1, and Cu 2+ 、Zn 2+ and Al 3+ The total molar concentration is 1.0 mol / L;

[0078] 2) Dissolve anhydrous sodium carbonate in water to obtain solution 2, Na + The concentration is 1.2 mol / L;

[0079] 3) Preheat solution 1 and solution 2 to 65±2°C respectively, perform co-current precipitation under stirring conditions, maintain the temperature at 65±2°C and the pH value at 9, and obtain a precipitate;

[0080] 4) The precipitate was stirred and aged for 0.5 h, filtered, washed, and dried at 260° C. for 8 h to obtain a Cu / ZnO / Al2O3 catalyst having a molar content of 55% copper.

[0081] The performance evaluation conditions of the catalyst were the same as those in Example 1. After 120 hours of steady state, the CO2 conversion rate was 13% and the methanol selectivity was 45%.

Claims

1. A Cu-NiZnFeO catalyst, characterized in that: It is based on Cu 2+ 、Zn 2+ 、Ni 2+ and Fe 3+ Mixed metal salt solution and CO3 2- and OH - The mixed alkaline solution of is used as a raw material, and a double drop method is used to prepare a quaternary hydrotalcite CuNiZnFe-LDH. The CuNiZnFe-LDH is calcined to obtain a catalyst precursor CuNiZnFe-LDO, and the catalyst precursor CuNiZnFe-LDO is then reduced in situ to obtain the catalyst precursor CuNiZnFe-LDO. The raw materials are weighed according to the following dosage relationship: the molar ratio of the total amount of Cu, Ni and Zn elements to the Fe element is 3:1, the molar percentage of Cu element in the total amount of Cu, Ni, Zn and Fe is 25-65%, and the molar percentage of Ni element in the total amount of Cu, Ni, Zn and Fe is 2-6%.

2. The Cu-NiZnFeO catalyst according to claim 1, characterized in that: The raw materials are weighed according to the following dosage relationship: the molar percentage of Cu element in the total amount of the four elements Cu, Ni, Zn and Fe is 25-45%, preferably 35-45%, more preferably 45%.

3. The Cu-NiZnFeO catalyst according to claim 1, characterized in that: The metal mixed salt solution is selected from Cu 2+ One of nitrates, chlorides or sulfates selected from Zn 2+ One of nitrates, chlorides or sulfates, selected from Ni 2+ One of nitrates, chlorides or sulfates selected from Fe 3+ The mixed alkaline solution is a mixed aqueous solution of one of nitrates, chlorides or sulfates; the mixed alkaline solution is a mixed aqueous solution of Na2CO3 and NaOH.

4. The Cu-NiZnFeO catalyst according to claim 1, characterized in that: CO3 2- The amount of substance satisfy: The OH - The amount of substance n OH- satisfy: in, Cu 2+ 、Ni 2+ 、Zn 2+ The total amount of substance; Fe 3+ The amount of substance.

5. A method for preparing the Cu-NiZnFeO catalyst according to claim 1, characterized in that: include: The mixed metal salt solution and the mixed alkali solution are mixed and reacted by a double drop method, and then aged to obtain a precipitate of CuNiZnFe-LDH. The CuNiZnFe-LDH is calcined to obtain a catalyst precursor CuNiZnFe-LDO, and then in-situ reduced to obtain a Cu-NiZnFeO catalyst.

6. The method for preparing the Cu-NiZnFeO catalyst according to claim 5, characterized in that: The temperature of the mixed reaction is 55-65°C, the mixed reaction time is 1 hour, and the pH of the mixed reaction is 9-10; the temperature of the aging is 55-65°C, and the aging time is 6-10 hours; the temperature of the calcination is 200-400°C, and the calcination time is 1-5 hours.

7. The method for preparing the Cu-NiZnFeO catalyst according to claim 5, characterized in that: The in-situ reduction environment is as follows: the reducing gas is a 50% H2 / N2 mixed gas, the reducing temperature is 200-300°C, and the reducing time is 2-8h.

8. The method for preparing the Cu-NiZnFeO catalyst according to claim 5, characterized in that: Also includes: After aging, the precipitate is separated by filtration or centrifugation, and the precipitate is washed with water until the pH value of the filtrate is 7, and then dried and ground in sequence to obtain CuNiZnFe-LDH.

9. Use of the Cu-NiZnFeO catalyst according to claim 1 in preparing methanol by hydrogenation of CO2.

10. A method for preparing methanol by hydrogenating CO2, characterized in that: include: The Cu-NiZnFeO catalyst according to claim 1 is used to catalyze the hydrogenation reaction of CO2 and hydrogen to obtain methanol; wherein the reaction gas is a mixture of H2 and CO2 in a volume ratio of 3:1 to 8:1, preferably a mixture of H2 and CO2 in a volume ratio of 3:1 to 3.5:1, the reaction temperature is 200 to 300°C, preferably 240 to 250°C, the reaction pressure is 2 to 5MPa, preferably 3 to 3.2MPa, and the reaction space velocity is 500 to 20000h -1 , preferably 6500~7600h -1 .